The Impact of Climate Change on Rubber Farmers' Income - Eva Juniar Andika; Amin Rejo; Puspitahati (PUCUK : Jurnal Ilmu Tanaman, 2025)
This study aims to analyze the impact of climate change on rubber production in Rambang District. Data was obtained through a survey of rubber farmers using a structured questionnaire. The results show that 90.9% of respondents experienced a drastic decline in production, 8.39% experienced a slight decline, 0.7% reported stable production, and no respondents reported an increase in production. These findings indicate that climate change has a significant impact on rubber productivity. This study emphasizes the need for adaptation efforts and better plantation management to mitigate the impacts of climate change.